Sodobni načini varstva pred porušitveno erozijo - Zemljič, Marijan (Gozdarski vestnik, 1999)
This article treats the situation in the field of natural hazard assessment inSlovenia and proposes further procedure of regulation. To determine the erosion threat zones, two types of documents are reasonable to be prepared: Erosion Threat Warning Plans and Maps of the Areas Endangered by Erosion. Warning plans can be readily prepared by careful processing of available data.However, they are less precise and can only give general directions for protection against erosion phenomena and proper management of the endangered areas. Detailed surveys of endangered areas and their precise zonings are given in the Maps of the Areas Endangered by Erosion. For elaboration of such maps, between 10 and 20 years of continuous professional work shall have been needed for the entire territory of Slovenia.
Keywords: erozija; varstveni ukrepi